Temporal Techniques: Dynamic Tracking of Nanomaterials in Live Cells. Issue 9 (8th November 2012) - Li, Wei; Liu, Ru; Wang, Yaling; Zhao, Yuliang; Gao, Xueyun
Abstract Temporal analytical techniques to track nanoparticles in live cell would provide rich information to well understand the biologic properties of nanoparticles in molecular level. Significant advances in fluorescence microscopy techniques with high temporal and spatial resolution allow single nanoparticles to label biomolecules, ions, and microstructures in live cells, which will address many fundamental questions in cell biology. This review highlights the real time tracking techniques for monitoring the movement of nanomaterials such as carbon nanotubes (CNTs), quantum dots (QDs), metal clusters, upconver‐sional nanomaterials, and polystyrene (PS) nanoparticles etc. in live cells. The biological properties of nanoparticles in live cells are also briefly summarized according to fluorescence microscopy studies.